Exploitation of labour or exploitation of commodities? - Deepankar Basu (University of Massachusetts, Department of Economics, 2020)
Attempts to use commodities to construct theories of value and use such value theory to claim that, in capitalism, commodities can be exploited, just like labour is, rest on two conceptual aws: (a) failure to distinguish between labour and labour-power; and (b) failure to distinguish labour-power and other commodities. One way to avoid these conceptual mistakes is to use the labour theory of value.
Keywords: B51; 330; labour theory of value; generalized commodity exploitation theorem